2021
DOI: 10.1080/19420862.2021.1955810
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive, homogeneous, and label-free protein-probe assay for antibody aggregation and thermal stability studies

Abstract: Protein aggregation is a spontaneous process affected by multiple external and internal properties, such as buffer composition and storage temperature. Aggregation of protein-based drugs can endanger patient safety due, for example, to increased immunogenicity. Aggregation can also inactivate protein drugs and prevent target engagement, and thus regulatory requirements are strict regarding drug stability monitoring during manufacturing and storage. Many of the current technologies for aggregation monitoring ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We previously developed a novel DSF-like method called the Protein-Probe [19][20][21][22]. The method is based on a Eu 3+ -labeled peptide probe, where a negatively charged peptide has minimal interaction with a folded protein, and the time-resolved luminescence (TRL) signal is low in the modulation solution containing a cyanine dye as quencher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed a novel DSF-like method called the Protein-Probe [19][20][21][22]. The method is based on a Eu 3+ -labeled peptide probe, where a negatively charged peptide has minimal interaction with a folded protein, and the time-resolved luminescence (TRL) signal is low in the modulation solution containing a cyanine dye as quencher.…”
Section: Introductionmentioning
confidence: 99%
“…This technique can avoid many of the problems related to conventional DSF dyes. The Protein-Probe enables similar stability, interaction, and buffer solution composition studies as conventional external thermal dyes, but with significantly improved sensitivity [19][20][21][22]. In addition, we have extensively studied KRAS and other GTPase proteins to enable monitoring of their functional properties [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of the used methods are time-consuming and expensive, as well as potentially require special instrumentation and expertise. We have previously introduced a label-free technique called the Protein-Probe, which has been applied for varying protein-related studies [ 35 38 ]. Using the protein-binding property of the Eu 3+ -probe, a key component of the Protein-Probe technique, we have now developed a virus particle quantitation assay, exploiting viral surface proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we present a novel virus particle counting method utilizing the recently developed label-free Protein-Probe technique [ 35 38 ]. In the Protein-Probe technique, the external Eu 3+ -peptide probe senses the concentration of monitored virus particles by an increase in the time-resolved luminescence (TRL) signal.…”
Section: Introductionmentioning
confidence: 99%
“…As with other DSF-type methods, thermal denaturation exposes protein inner regions and promotes the binding of the Eu-probe, which can be monitored with an increase in TRL-signal (Figure ). We have demonstrated that the protein-probe method is highly sensitive and can detect protein interactions, stability, aggregation, and enzyme activities with 100-fold higher sensitivity than the commonly used SYPRO Orange. , In this study, we describe our scientific efforts to further improve the sensitivity and simplicity of the assay by modifying the quencher structure; 13 quencher molecules were prepared and studied using the protein-probe platform. Our results demonstrate significant improvements in assay performance, enabling the detection of protein stability and protein–ligand interaction using a one-step peptide-probe protocol at neutral pH buffers (Figure ).…”
Section: Introductionmentioning
confidence: 99%